DESIGN, OPTIMISATION AND EVALUATION OF PIROXICAM FAST DISSOLVING TABLETS EMPLOYING STARCH TARTRATE-A NEW SUPERDISINTEGRANT - KUMAR, R. SANTOSH; GHOSH, ANKITA (International Journal of Applied Pharmaceutics, 2019)
Objective: To enhance the solubility of poorly soluble drugs by evaluating starch tartrate as a superdisintegrant in the formulation of fast dissolving tablets by employing 23 factorial design. Methods: Starch tartrate was synthesized by gelatinization process. The physical and micromeritic properties were performed to evaluate the synthesized starch tartrate. The fast dissolving tablets of piroxicam were prepared by using starch tartrate as a superdisintegrant in different proportions by direct compression technique using 23 factorial design. The drug content, hardness, friability, disintegration time and other dissolution characteristics like percent dissolved in 5 min (PD5), dissolution efficiency in 5 min (DE5%) and first-order rate constant (K1) were used in the evaluation of prepared fast dissolving tablets. Results: The superdisintegrant starch tartrate prepared was found to be fine, free-flowing slightly crystalline powder. Starch tartrate exhibited good swelling in water. The study between piroxicam and starch tartrate was shown the absence of interaction by fourier transform infrared spectra (FTIR) and differential scanning calorimetry (DSC). The drug content (99.83±0.56 %), hardness (3.7–3.9 kg/sq. Cm), and friability (0.12-0.15%) have been effective with regard to all the formulated fast dissolving tablets employing starch tartrate. The disintegration time of all the formulated fast dissolving tablets (FDTs) was found to be in the range of 12±0. 01 to 4500±0.02s. The optimized formulation F6 has the least disintegration time i.e., 12±0. 01s. The In vitro wetting time of the formulated tablets was found to be in the range of 35±0.09 to 1624±0.02s. The In–Vitro wetting time was less (i.e., 90s) in optimized formulation F6. The water absorption ratio of the formulated tablets was found to be in the range of 60±0.12 to 65±0.15%. The cumulative drug dissolved in the optimized formulation F6 was found to be 99.32±0.09% in 10 min. Conclusion: The dissolution efficiency of piroxicam was enhanced when starch tartrate was found to be a superdisintegrant when combined with crospovidone and, hence it could be used in the formulation of fast dissolving tablets to provide immediate release of the contained drug within 10 min.